2012
DOI: 10.2174/138955712798995039
|View full text |Cite
|
Sign up to set email alerts
|

Indolinones as Promising Scaffold as Kinase Inhibitors: A Review

Abstract: Kinases are probably the most important signaling enzymes, which represent about 20% of the druggable genome. Currently, more than 150 kinases are known. So, kinase inhibition therapy has become a very important area of drug research since most of our diseases are related to intra or intercellular signaling by kinases. Indole alkaloids are extensively studied for their biological activities in several pharmaceutical areas, including, for example, antitumor. Among this chemical family, indolinone displays very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 82 publications
0
30
0
Order By: Relevance
“…Indeed, the structurally simpler indolin-2-one predecessor semaxanib (SU5416) 2 underwent a Phase III clinical trial for advanced colorectal cancer. 6 In recent work, we…”
Section: Synthesis and Preliminarymentioning
confidence: 99%
“…Indeed, the structurally simpler indolin-2-one predecessor semaxanib (SU5416) 2 underwent a Phase III clinical trial for advanced colorectal cancer. 6 In recent work, we…”
Section: Synthesis and Preliminarymentioning
confidence: 99%
“…1H-indole-2,3-dione derivatives possess av ariety of biological activities, including antitumor activity [2].I ntroduction of substituents at the 3-and 5-positions of the indolin-2-one ring have recently led to many derivatives possessing more potent antiumor activities [3,4].Inaddition, the introduction of an alkyl group or aryl group at the Natom of indolin-2-ones enhanced their cytotoxicity againstavarietyofcancercelllines [5,6]. Herein, we report thecrystal structure of oneofthe derivateswhich maybea potential anticancer agent.…”
Section: Discussionmentioning
confidence: 99%
“…1H-indole-2,3-dione derivatives have driven much attention for their bioactivities on anti-HIV [1], anticonvulsant[ 2] and antitumor activities [3,4].Ithas been reported that the introduction of substituents at the Natom of indolin-2-ones enhances their cytotoxicity against avariety of cancer cell lines [5,6]. In an attemptt oo btain compounds that might also exhibit antitumor properties, we carried out the reaction of 6-bromo-1-(2-bromoethyl)indoline-2,3-dione with an excess of morpholine.…”
Section: Discussionmentioning
confidence: 99%